Space based infrared observations for space situational awareness - Dodero, Matteo (Cranfield University, 2025)
This thesis explores the feasibility of using infrared sensors for space-based space situ- ational awareness in low earth orbit. The goal is to assess if the thermal radiation of targets can be detected, therefore rendering them visible, even under unfavourable illu- mination conditions i.e. during eclipse. This thesis is done in collaboration with Arca Dynamics. After a literature review, the relevant sensor requirements are outlined and bolometer cameras are chosen because of their cost effectiveness. INO’s High-Definition Infrared Space Camera Core is selected as the chosen sensor. Next, the radiometric signa- tures of targets are modelled and a simplified model to assess detectability is constructed. This model is used to assess the limitations of the technology showing that detectability is highly dependent on target temperature and detection is feasible only for large objects (at least larger than 8 m2) at temperatures reached during eclipse. Next, a more complete bo- lometer model is developed that includes important effects such as point spread function, thermal time constant, integration and amplification, and a noise model. This model is then used in the simulation pipeline that allows us to simulate different target and observer scenarios, assess detectability, and generate synthetic images. A case study is presented using the satellite Cartosat-1 which shows that the object is detectable at distances up to 238 km. This study shows that detection of objects during eclipse is feasible, but only for relatively large objects at limited ranges. Target temperatures and relative kinematics are also crucial factors that influence detection. The model still needs to be validated to ensure its fidelity to reality. However, the behaviour of this model is in agreement with similar work in the literature.
Spiller, Dario - Industrial Supervisor - Arca Dynamics
Keywords: Bolometer; object detection; synthetic images; sensor model; SST; Signal-to-noise ratio